Inverse Compton radiation: a novel x-ray source for K-edge subtraction angiography?. (11th September 2019) - Paternò, G; Cardarelli, P; Gambaccini, M; Serafini, L; Petrillo, V; Drebot, I; Taibi, A
Abstract: Coronary angiography is clinically used worldwide to diagnose diseases of coronary arteries. Despite its effectiveness, this technique is quite invasive and it is associated with significant risks due to the arterial catheterisation needed to inject the contrast agent. A valid alternative is using the K-edge subtraction (KES) method, which is based on the subtraction of two images acquired at energies bracketing the K-edge of the contrast element. The enhanced sensitivity of KES allows the intravenous injection of the contrast agent, thus reducing the risks of catheterisation. This technique can be effectively implemented by using intense and quasi-monochromatic x-ray beams. Synchrotron radiation has been proven to work well for this purpose, but its cost and size prevent a widespread clinical application. Inverse Compton sources are among the most promising innovative sources of intense and quasi-monochromatic x-rays. These sources are intrinsically more compact than those based on synchrotron radiation. In this work, the potential application of inverse Compton radiation to KES angiography is investigated. To this purpose, after a short review of the physics behind the inverse Compton process, an analytical framework is described. The proposed model is based on the application of the KES algorithm to calculate the SNR of details inside a suitable mathematical phantom. That allowed us to identify the characteristics of an inverse Compton source required for KES imaging. In particular, it was estimated that a photon fluence of 10 8 ph mm −2 is necessary to detect signals of clinical interest. Novel sources based on inverse Compton promise to achieve this requirement with an acquisition time of few hundreds of ms. This feature, together with compactness, broad two-dimensional radiation field, absence of harmonic contamination and the ability to deliver high photon fluxes also at high energies, makes this kind of sources promising for KES angiography and other diagnostic applications.